Anhedonia as a basic syndrome and a target for treatment for depressive disorder - G. E. Mazo; A. O. Kibitov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
The article presents an analytical review aimed at determining the effect of anhedonia on the course and therapeutic prognosis of depression. Currently, there is no specific pharmacological approach to the treatment of anhedonia in depression.It is clear all antidepressants that affect the symptoms of depression in general act to a certain extent on anhedonia. Modern views on the biological mechanisms involved in the formation of anhedonia are described, on the basis of which a search for drugs with anti-anhedonic activity is possible. Vortioxetine can be considered as an antidepressant with a specific anti-anhedonic effect.